Superalloys 2004 (Tenth International Symposium) 2004
DOI: 10.7449/2004/superalloys_2004_769_778
|View full text |Cite
|
Sign up to set email alerts
|

New Phases in Ruthenium-Coating Single-Crystal Superalloys

Abstract: Phases present in a series of model ruthenium containing Ni-base single crystal superalloys were investigated in both as-solidified and heat-treated crystals. Three unusual Ru-rich phases have been identified including a L2 1 Heusler phase with a composition of Ru 2 AlTa, a B2 RuAl phase and a hcp Re(Ru)-rich phase. These phases have been characterized in terms of the microstructure, composition, crystallography, three-dimensional morphology and distribution within the dendritic microstructure via X-ray, SEM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Ru has been shown by Chao [29] to substitute favourably on the Ni lattice site in NiAl. However the maximum solubility of Ru in γ' is approximately 5 at% [30], hence interestingly, in the UCSX2-5Ru alloy where a SRZ was present (after both 900 and 1100°C exposures) precipitates of RuAl (akin to those identified by Feng et al [31]) could be found within the SRZ γ' matrix, as shown in Figure 14 and Figure 15. Matrix dilution precluded the precise compositional analysis by EDX of 'RuAl' precipitates formed in aluminized UCSX2-5Ru after 500h at 1100°C.…”
Section: Test Conditionsmentioning
confidence: 72%
“…Ru has been shown by Chao [29] to substitute favourably on the Ni lattice site in NiAl. However the maximum solubility of Ru in γ' is approximately 5 at% [30], hence interestingly, in the UCSX2-5Ru alloy where a SRZ was present (after both 900 and 1100°C exposures) precipitates of RuAl (akin to those identified by Feng et al [31]) could be found within the SRZ γ' matrix, as shown in Figure 14 and Figure 15. Matrix dilution precluded the precise compositional analysis by EDX of 'RuAl' precipitates formed in aluminized UCSX2-5Ru after 500h at 1100°C.…”
Section: Test Conditionsmentioning
confidence: 72%
“…First, Ru additions may substantially alter the thermodynamics of the superalloy system, decreasing the driving force for precipitation of undesirable phases such as the , P, and R phases. Conversely other new phases may appear in equilibrium with the and the ' phases at high temperatures; this is the subject of a companion paper in this volume [14]. If the -' phase equilibrium is modified, partitioning of elements to the phases may be altered, resulting in changes in the -' lattice misfit and precipitate morphology.…”
Section: Introductionmentioning
confidence: 99%
“…3. According to the SEM and TEM observation, it is judged as NiAl base b phase, which has been seldom reported except that it was found by Feng et al 15 in a single crystal superalloy with high Ru content (9?6 wt-%). In these test alloys, only in 3Ru alloy, the b phase was found, which illustrates that the a 0Ru alloy; b 1?5Ru alloy; c 3Ru alloy 1 Dendrite microstructures of alloys with different contents of Ru Differential thermal analysis DSC analysis was employed to investigate the solidification sequence and transformation temperatures in three alloys with the heating rate of 5 K min 21 .…”
Section: Resultsmentioning
confidence: 93%